PENERAPAN METODE HILL CLIMBING UNTUK MENDIAGNOSA PENYAKIT GANGGUAN SARAF BERBASIS ANDROID - Nicolina Djiu; Syaiful Rahman; Izmy Alwiah Musdar (STMIK KHARISMA Makassar, 2019)
This research intend to apply Hill Climbing method to system for diagnose nervous disorders by making an application using android programming. In this system there is symptoms of nervous diseases data which the authors get directly from the results of interviews with a neurologist in the place where author doing research. Hill Climbing method is used to look for possible diseases of nervous disorders by observing the symptoms experienced by the user. The results of the implementation of the system by applying Hill Climbing method to diagnose nervous disorders showed that this method can provide the result of temporary diagnosis in the form of early information about the possibility of disease which suffered by the user.